English Versus Native Language on Social Media: International Students’ Cultural Adaptation in the U.S. - Tu, Haijing (Journal of International Students, 2018)
The number of international students studying in the U.S. has substantially increased in the digital age. Do having access to content in their native language work for or against their adaptation to American culture? In order to address this question, this research employed focus groups and interviews containing a total of 12 international students in 2016. Qualitative data analysis then revealed international students’ language preferences on social media as well as the functions performed by each language. Their cultural adaptation was studied by coding data into language preference, friendship, acts and social norms, and characteristics and values. Social media proved very effective in connecting international students with their home culture, but it was not as equally effective in connecting them with their host culture.